Antimicrobial activities of endophytic bacteria isolated from Ageratum conyzoides Linn. - NARUMON BOONMAN; JARUWAN CHUTRTONG; CHANATE WANNA; SIRIPHAN BOONSILP; SUPATRA CHUNCHOB (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Boonman N, Chutrtong J, Wanna C, Boonsilp S, Chunchob S. 2023. Antimicrobial activities of endophytic bacteria isolated from Ageratum conyzoides Linn. Biodiversitas 24: 1971-1979. Endophytic bacteria were isolated from various parts of Ageratum conyzoides Linn. Total 35 isolates were obtained which were consisting of eight isolates from the roots (AconR1-AconR8), nine isolates from the stems (AconS1-AconS9), seven isolates from the leaves (AconL1-AconL7) and 11 isolates from the flowers (AconF1-AconF11). These endophytic bacteria were examined for their antimicrobial activities against human pathogenic bacteria and fungi. The AconR2 and AconR4 inhibited the growth of Shigella flexneri and Salmonella enterica ser. typhi, whereas Escherichia coli was only inhibited by AconR2. For the antifungal activities assay, all isolated endophytic bacteria revealed no effect on Candida albicans, while six endophytic isolates exhibited more than 80% mycelial growth inhibition against Microsporum canis. These highly effective isolates were identified by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS). The Bruker scores revealed that AconR2 and AconR4 were identified as Pseudomonas aeruginosa, AconS1 and AconS6 were classified as Enterobacter asburiae, Acon L5 and Acon F9 were identified as Bacillus cereus. The results indicated that these endophytic bacteria isolated from A. conyzoides effectively inhibited the growth of human pathogenic filamentous fungi and showed promise for further development as novel antifungal agents.